Kulturowa tożsamość książki, red. Anna Cisło, Agnieszka Łuszpak, Wrocław: Wydawnictwo Uniwersytetu Wrocławskiego 2014, s. 300 (Acta Universitatis Wratislaviensis, No 3582) - Jacek Wojciechowski (Biblioteka)
Recenzja